2015
DOI: 10.1039/c5sm01431j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of rationally designed “surf-tides” to a liquid-crystal interface

Abstract: The interfacial adsorption of proteins in surfactant laden systems occurs both in nature and industrial processing, yet much of the fundamental behavior behind these systems is still not well understood. We report the development of a system that monitors optical transitions of a liquid-crystalline/aqueous interface to examine the dynamics of adsorption of two rationally designed model peptide molecules. The two molecules synthesized in this study were both designed to become surface-active upon folding and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Of relevance to the study reported herein, a number of past studies of LCs have focused on understanding the equilibrium orientations of LCs at aqueous interfaces decorated by amphiphiles such as phospholipids (1,2-dilauroyl- sn -glycerol-3-phosphocholine (DLPC), Scheme b), ,,, synthetic surfactants (e.g., dodecyltrimethylammonium bromide (DTAB)), ,, or peptide–polymer amphiphiles. , Adsorption of these amphiphiles from aqueous dispersions results in reorientation of the LCs in a manner that is dependent on the structure and the concentration of the amphiphiles. ,, Various factors have been identified to influence the orientations of LCs at amphiphilic-decorated aqueous interfaces, including interdigitation of the aliphatic tails of the amphiphiles into the LCs, ,,,, disorder induced in the LCs due to frustrated packing of mesogens at the interface, , and electrical double layer interactions. , …”
Section: Introductionmentioning
confidence: 99%
“…Of relevance to the study reported herein, a number of past studies of LCs have focused on understanding the equilibrium orientations of LCs at aqueous interfaces decorated by amphiphiles such as phospholipids (1,2-dilauroyl- sn -glycerol-3-phosphocholine (DLPC), Scheme b), ,,, synthetic surfactants (e.g., dodecyltrimethylammonium bromide (DTAB)), ,, or peptide–polymer amphiphiles. , Adsorption of these amphiphiles from aqueous dispersions results in reorientation of the LCs in a manner that is dependent on the structure and the concentration of the amphiphiles. ,, Various factors have been identified to influence the orientations of LCs at amphiphilic-decorated aqueous interfaces, including interdigitation of the aliphatic tails of the amphiphiles into the LCs, ,,,, disorder induced in the LCs due to frustrated packing of mesogens at the interface, , and electrical double layer interactions. , …”
Section: Introductionmentioning
confidence: 99%
“…Concerning protein-based studies, careful investigation using LC has been carried out by several groups to understand the interfacial phenomenon regarding protein binding events and consequent lateral organization of the biomolecules at LC–aqueous interfaces. It is well-known that proteins trigger a negligible change in orientations of LC; therefore, to achieve an optical signal for protein, it is important, prior to protein adsorption, to modify the LC–aqueous interface with amphiphiles that promote homeotropic orientations of LC. Thus, previous protein-related studies at LC–aqueous interfaces vastly comprise linear amphiphiles such phospholipids and conventional water-soluble surfactants and polymers. Recently, Yang et al reported the synthesis and examination of the self-assembly behavior of a linear lipopeptide at LC–aqueous interfaces . Regarding protein adsorption studies, we recently made an advancement using a cyclic lipopeptide, polymyxin B (PmB), which could trigger a homeotropic ordering of LC supported by topological flexibility of its cyclic peptidic headgroup and the linear acyl tail .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a range of past studies using LC sensors with LC-aqueous interfaces have reported observations of orientational transitions of LCs triggered by the adsorption or reorganisation of amphiphilic molecules at the interface [15,[48][49][50][51]. The changes in orientations of the LCs reflect, in part, the interaction of LC mesogens with aliphatic tails of the amphiphiles and depend on the structure and concentration of the amphiphiles [13,16,49,52] as well as the solution conditions [22]. From reference [37,39].…”
Section: Beyond Equilibrium: Design Of Lc Biological Sensors Based On Non-equilibrium Interfacial Phenomenamentioning
confidence: 99%